2017
DOI: 10.1016/j.nanoen.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-long cycle life, low-cost room temperature sodium-sulfur batteries enabled by highly doped (N,S) nanoporous carbons

Abstract: Efficiency, cost, and lifetime are the primary challenges for stationary energy storage with vanadium-redox flow and sodium-sulfur batteries as promising options. In particular, room temperature sodium-sulfur battery systems offer the potential for safe, simple, low-cost and high energy density storage, but the high reactivity or solubility of sodium polysulfides in common liquid electrolytes for carbonates or glycols, respectively, leads to rapid performance loss on cycling. Herein, we demonstrate a robust ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
156
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(159 citation statements)
references
References 62 publications
3
156
0
Order By: Relevance
“…Interestingly, the precycle capacity of untreated NaS with FEC is approximately two times higher than that of untreated NaS without FEC (Figure 3b), presumably because NaF is spontaneously formed on the sulfurcarbon composite cathode before the electrochemical reaction and can temporarily inhibit the initial polysulfide dissolution ( Figure S4, Supporting Information). Compared with previously reported researches (Figure 3f), [10,11,13,16,28,29] ET-NaS with FEC shows outstanding active material utilization and cycling stability at high current density (1 A g −1 ) (Table S1, Supporting Information). Figure 3c shows the charge-discharge profile of untreated NaS and ET-NaS with FEC at 0.4 A g −1 .…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Interestingly, the precycle capacity of untreated NaS with FEC is approximately two times higher than that of untreated NaS without FEC (Figure 3b), presumably because NaF is spontaneously formed on the sulfurcarbon composite cathode before the electrochemical reaction and can temporarily inhibit the initial polysulfide dissolution ( Figure S4, Supporting Information). Compared with previously reported researches (Figure 3f), [10,11,13,16,28,29] ET-NaS with FEC shows outstanding active material utilization and cycling stability at high current density (1 A g −1 ) (Table S1, Supporting Information). Figure 3c shows the charge-discharge profile of untreated NaS and ET-NaS with FEC at 0.4 A g −1 .…”
mentioning
confidence: 56%
“…[7] Additionally, the high-temperature operation results in safety, cost, and efficiency concerns. [9][10][11][12] To prevent the shuttle effect, several research studies have reported various attempts: (i) encapsulation with/infiltration into porous carbon, [13] (ii) coating of the cathode with conductive polymers, [14] (iii) formation of multiple metal oxides, [15] and (iv) development of a membrane to impede polysulfide diffusion to the anode. [9,10] However, RT-NaS still faces critical obstacles to practical use, such as the low electrical conductivity of sulfur, large volume expansion (≈170%), loss of active materials, etc.…”
mentioning
confidence: 99%
“…Nowadays, the family of low-dimensional carbon allotropes includes numerous members [6], supporting a wide range of applications from electronics [7] to medicine [8], from optics [9] to environment protection [10], from energy storage [11][12][13][14] to catalysis [15]. While the synthesis strategies as well as the key structural features have already been extensively investigated, the focus has now shifted toward tuning the textural and electronic properties of these materials to optimize their performances in the pursuit of technological progress and manufacturing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to explore and develop an energy storage system which is capable of supplementing existing limited energy density and long cycle life of lithium-ion battery (LIBs). [8,9] Second, Na-S batteries have a higher volume expansion than lithium-sulfur batteries (LSBs), which makes the cathode structure of Na-S batteries prone to collapse. [4][5][6][7] These advantages make the room-temperature Na-S battery have broad application prospects in large-scale power grid equipment.…”
mentioning
confidence: 99%